Effects of Licorice on Relief and Recurrence of Menopausal Hot Flashes - Nahidi, Fatemeh (Shaheed Beheshti University of Medical Sciences, 2012)
Vasomotor hot flash is the most common and distressful complication of menopausal women. Its treatment is the most frequent clinical challenge. As a result, an effective and harmless therapy is needed. This double-blind controlled clinical trial was conducted to determine the effects of licorice roots on the relief and recurrence of hot flash in menopausal women referring to the healthcare centers affiliated to Shahid Beheshti Medical University in 2010. Ninety menopausal women complaining of hot flash were selected by reviewing their records in healthcare centers and randomly divided into 2 licorices (3 capsules daily containing 330 mg licorice abstract) and placebo (3 capsules daily containing 330 mg starch) groups over the 8 weeks of intervention and 4 weeks of follow-up. Two weeks prior to the intervention, the severity as well as frequency of hot flashes and the foods taken were asked and documented with questionnaires and data sheets. Data within and between the groups were analyzed by ANOVA with repeated measurements and t-test respectively. Means of age and body mass index (BMI) of the subjects in licorice and placebo groups were 53 ± 3.2, 52.69 ± 2.8, 24.71 ± 3.2 and 23.61 ± 3.3, respectively. The groups were similar in terms of intervening variables. The frequency of hot flash decreased significantly in the experimental (than the placebo group) and this lasted for 2 weeks after the administration of the capsules. The severity of hot flash decreased in the licorice group as well. This decrease was also seen in the placebo group in the first week of the intervention. Decreased hot flash in the placebo group was only significant after the 1(st) week of intervention compared to the previous period. Recurrence of frequency and severity of hot flashes occurred 2 weeks after the termination of therapy. The significant decrease in the placebo group after the 1(st) week of the intervention may be attributed to the psychological effects of placebo. Licorice roots decreased the frequency and severity of hot flashes. The administration of this harmless, inexpensive herb well accepted by the menopausal women together with the appropriate and continuous physical activities and consumption of dairy products are recommended for relieving this complication.